The impact on brand equity of crop-based food brands that deploy genetic crop modification methods as a result of persisting drought conditions: a triangulation study based on Western Cape millennial consumers - Ryan, Kristen (The IIE, 2018)
Brand transparency plays an important role in building brand equity and is continuing to play an equally important part in the development of trust between the brand and it’s consumer, and is highly considered by millennials when deciding what product to buy. The persisting Western Cape drought has placed immense pressure on crop-based food brands to find alternative water-saving farming methods grow maize meal under harsh weather conditions. Data was gathered through semi-structured surveys with with Western Cape millennial consumers aged 22-37, in order to draw a conclusion about their willingness to support a crop-based food brand that isn’t being transparent. Findings show that the purchase behaviour of Western Cape Millennials are driven by how transparent crop-based food brands are about their production methods. Transparency is important to Western Cape millennial consumers and a lack of which can alter their purchase behaviour. By ensuring transparency in all that it does, a brand is able to establish trust with it’s consumers and thereby build meaningful relationships with them. Maize meal is one of the staple foods in South Africa and with the rise of genetically modified (GM) crop production methods as a result of the persisting drought and the negative perceptions held by Western Cape Millennial Consumers, it has become more important now than ever that a brand makes a point to inform their consumers of any possible changes that may or have occurred in the production of their maize meal. The results of the proposed research can help crop-based brands to understand the increasingly important role that brand transparency plays in the development of strong brand equity in context of the persistent drought conditions.
Keywords: Brand building; Brand equity; Millennials; Food brands; Crop-based food brands; Drought; Brand transparency